Surface Topography and Biocompatibility of cp–Ti Grade2 Fabricated by Laser‐Based Powder Bed Fusion: Influence of Printing Orientation and Surface Treatments. Issue 7 (16th December 2022) - Petrusa, Jelena; Meier, Benjamin; Grünbacher, Gerda; Waldhauser, Wolfgang; Eckert, Jürgen
Abstract : The selective laser melting process, commonly known as laser‐based powder bed fusion (LB‐PBF), enables the production of structures with unprecedented degrees of freedom that represents an excellent condition for development of metallic implants for biomedical applications. Herein, the effects of laser energy density on relative density and microstructure (presence of internal defects) of cp‐TiGd2 fabricated by LB‐PBF are studied. Additionally, the influence of printing orientation and different surface treatments on surface topography and biocompatibility are investigated. The aim of the research is to develop additive manufacturing process parameters that can achieve full density of cp‐TiGd2 with satisfactory biocompatibility, as a low‐cost alternative to biomedical materials such as Ti–6Al–4 V and Ti–6Al–7Nb. A wide range variation of process parameters leads to an optimized process with high density up to 99.97 ± 0.008%, improved surface roughness, and noncytotoxicity in horizontal and inclined as‐built condition, as well as in Al2 O3 (blasting angle 0°) condition. Abstract : Herein, the effects of laser energy density on relative density and microstructure of commercially pure titanium grade2 fabricated by laser‐based powder bed fusion are studied. A wide range variation of process parameters leads to an optimized process with high density up to 99.97 ± 0.008%, improved surface roughness, and noncytotoxicity.